2004
DOI: 10.1038/sj.jp.7211114
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Early Total Parental Nutrition in Low-Birth-Weight Infants

Abstract: This study shows that aggressive intake of AA and IL can be tolerated immediately after birth by VLBW infants. Also, ETPN significantly increased positive nitrogen balance and caloric intake, without increasing the risk of metabolic acidosis, hypercholesterolemia, or hypertriglyceridemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
200
2
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 246 publications
(217 citation statements)
references
References 34 publications
8
200
2
7
Order By: Relevance
“…However, the number of patients studied is too small in both studies to detect significant difference in these outcomes. Other studies have reported 'early administration of AA'; 17,[21][22][23][24] however, the intervention group in those studies were similar to the late AA groups in these studies 12,13 and our study. Postnatal malnutrition has been increasingly implicated not only with postnatal growth but also with neurodevelopmental outcomes and certain adult-onset diseases including diabetes mellitus and hypertension.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…However, the number of patients studied is too small in both studies to detect significant difference in these outcomes. Other studies have reported 'early administration of AA'; 17,[21][22][23][24] however, the intervention group in those studies were similar to the late AA groups in these studies 12,13 and our study. Postnatal malnutrition has been increasingly implicated not only with postnatal growth but also with neurodevelopmental outcomes and certain adult-onset diseases including diabetes mellitus and hypertension.…”
Section: Discussionsupporting
confidence: 73%
“…7,25 -29 Previous concerns of metabolic acidosis and hyperammonemia 10,11 have been challenged in recent studies of improved AA formulations. 12,21,23,24 However, a word of caution is warranted as our study and the study by Te Braake et al 13 identified clinically unimportant but statistically significant differences in the values for pH, HCO 3 and base deficit indicative of metabolic acidosis. Overall, from a practical standpoint with the preparation of 'stock' solutions of 5, 7.5 and 10% dextrose and 2 g of AA/100 ml we are now able to initiate AA in the resuscitation room.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations